Super-resolution probe to monitor HNO levels in the endoplasmic reticulum of cells - Ali, Firoj; Sreedharan, Sreejesh; Ashoka, Anila Hoskere; Saeed, Hiwa K.; Smythe, Carl G. W.; Thomas, Jim A.; Das, Amitava (Analytical Chemistry, 2017)
Selective detection of nitroxyl (HNO), which has recently been identified as a reactive nitrogen species, is a challenging task. We report a BODIPY-based luminescence ON reagent for detection of HNO in aqueous solution and in live RAW 264.7 cells, based on the soft nucleophilicity of the phosphine oxide functionality toward HNO. The probe shows high selectivity to HNO over other reactive oxygen/nitrogen and sulfur species. Luminescence properties of the BODIPY-based chemodosimetric reagent make it an ideal candidate for use as a reagent for super-resolution structured illumination microscopy. The viability of the reagent for biological in vivo imaging application was also confirmed using Artemia as a model.